Educational Structures in Medieval Europe: Insights from Schools and Universities - Achilovich, Abdujabborov Shakhboz (Journal of Innovation in Education and Social Research, 2025)
This article explores the educational structures of medieval Europe, focusing on the role of schools and universities in shaping intellectual life during the period. Despite the pivotal role of education in medieval society, the development of educational institutions and their influence on broader European culture remain underexplored in existing scholarship. This study addresses this gap by examining the evolution of educational structures in medieval Europe, with particular attention to the rise of universities and their interaction with religious and political authorities. Using a historical-analytical methodology, the article investigates primary sources, including medieval university charters, religious texts, and historical accounts, to reconstruct the educational landscape of the time. Key findings reveal that medieval schools and universities were not merely centers of academic learning but also significant hubs of social, cultural, and political influence. The establishment of universities in key European cities helped formalize education, shifting the focus from monastic schools to more secular and diverse curricula. The results indicate that medieval educational institutions played a crucial role in preserving and transmitting knowledge, fostering intellectual movements that laid the groundwork for the Renaissance. Furthermore, the study highlights the complex relationship between education and power, with political and religious authorities exerting considerable control over educational content and access. The implications of this study suggest that understanding the educational structures of medieval Europe can provide valuable insights into the development of modern educational systems, offering lessons on the integration of education with societal needs and governance.